Broadband modulated absorption/emission technique to probe sooting flames: Implementation, validation, and limitations - Guibaud, A.; Citerne, J.M.; Orlac’h, J.M.; Fujita, O.; Consalvi, J.-L.; Torero, J.L.; Legros, G. (Proceedings of the Combustion Institute, 2019)
A new optical setup and its associated post-processing have been designed in an effort to map soot related quantities in an axisymmetric flame spreading over solid samples in microgravity environment where setup compactness constraints are stringent. Extending the well-established spectral modulated absorption/emission (S-MAE) technique that uses lasers as light sources together with a sophisticated optical arrangement, LEDs have been associated with broadband optics to enable the broadband modulated absorption/emission (B-MAE) technique. The design and the cautious assessment of the original B-MAE setup are reported in the present paper. Algorithms that need to be reformulated for broadband integration are first validated retrieving both two-dimensional soot temperature and volume fraction fields produced by numerical simulations. Then, these fields are measured with both B-MAE and S-MAE techniques in a largely documented steady laminar non-premixed coflow ethylene/air flame established at normal gravity. Thus, outputs delivered by the B-MAE technique can be compared with those obtained with the S-MAE setup. Both soot temperature and volume fraction are shown to be decently measured by the B-MAE technique. As the spread of the non-buoyant flames to be investigated in the near future is especially driven by radiative heat transfer, the discrepancies between both techniques outputs are commented in the light of the fields of local radiative loss computed from the fields measured by both techniques. As a result, the fields delivered by the B-MAE technique are expected to provide ground-breaking insights into the control of flame spread in the absence of buoyancy, therefore manned spacecraft fire safety.